2010
DOI: 10.3201/eid1603.091333
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia,Ehrlichia, andRickettsiaspp. in Ticks Removed from Persons, Texas, USA

Abstract: Some tick-borne agents may pose yet-unknown public health risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 33 publications
8
75
1
Order By: Relevance
“…For example, in 2001, when B. lonestari, an RF group Borrelia species found in A. americanum, was tentatively linked to a case of southern tick-associated rash illness (STARI) (5), HTTKP testing was modified to include testing for B. lonestari (21)(22)(23)(24). However, epidemiological studies of STARI patients did not support the hypothesized link between STARI and B. lonestari (6,7,25), so targeting of this Borrelia species in the HTTKP ended in 2009.…”
mentioning
confidence: 99%
“…For example, in 2001, when B. lonestari, an RF group Borrelia species found in A. americanum, was tentatively linked to a case of southern tick-associated rash illness (STARI) (5), HTTKP testing was modified to include testing for B. lonestari (21)(22)(23)(24). However, epidemiological studies of STARI patients did not support the hypothesized link between STARI and B. lonestari (6,7,25), so targeting of this Borrelia species in the HTTKP ended in 2009.…”
mentioning
confidence: 99%
“…Testing of TDSHS samples by UTNHSC is an ongoing endeavour and the study reported here not only includes the 903 ticks collected between 2004 and 2008 in our original study (Williamson et al, 2010), but also includes 555 additional tick submissions collected between 2008 and 2010. The occurrence data were aggregated by TDSHS to the zip-code level.…”
Section: Habitat Probability Mappingmentioning
confidence: 99%
“…The occurrence data were aggregated by TDSHS to the zip-code level. Molecular screening for tick-borne pathogens, including R. rickettisii, was performed at UNTHSC using the method of Williamson et al (2010). These data were spatially tagged with the zip code of where the tick was encountered.…”
Section: Habitat Probability Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…17,20,[34][35][36][37][38][39][40][41][42][43][44] Because of these large differences in prevalence, exposure to R. rickettsii may be rare relative to exposure to "Ca. Rickettsia amblyommii".…”
Section: Discussionmentioning
confidence: 99%